EXPERIMENTAL INVESTIGATION OF FORCED CONVECTION HEAT TRANSFER WITH SINGLE AND HYBRID NANOFLUIDS FOR ENERGY TRANSPORT ENHANCEMENT - AKILU, SULEIMAN (2018)
Advanced heat transfer fluid preparation by dispersion of two different materials containing nanometer size particles is a relatively recent development in the field of heat transfer.